Pengaruh Profitabilitas, Pendapatan Mudharabah, dan Bonus Wadiah terhadap Dana Zakat (Studi Kasus Bank Umum Syariah di Indonesia) - Asnatul Kharima (Fakultas Ekonomi dan Bisnis, 2025)
The purpose of this research is to analyze and test the influence of profitability, mudharabah income, and wadiah bonuses on zakat funds in BUS in Indonesia for the period 2021-2024. The research method used is a quantitative approach with an explanatory research design. The data used are secondary data obtained from the Financial Services Authority (OJK) and the related company websites. The sample was selected using purposive sampling techniques, resulting in 6 BUS registered with the Financial Services Authority (OJK). This research processes and analyzes data using EViews 12 software. Data analysis is conducted using the panel data regression method with the selected Fixed Effect Model (FEM). The research results show that partially, the profitability and mudharabah income variables have a positive and significant effect on zakat funds. Conversely, the wadiah bonus variable does not show a significant effect on zakat funds. Simultaneously, the three independent variables have a significant effect on zakat funds with an Adjusted R-squared value of 0.765729, which means that 76.5% of the zakat fund variable can be explained by these three variables. The conclusion that can be drawn is that profitability and mudharabah income are determining factors in the distribution of zakat funds by BUS in Indonesia, whereas wadiah bonuses are not a factor that influences zakat funds of Sharia Commercial Banks in Indonesia during the period 2021-2024.
Entry oleh Arif 2026 April 01
Keywords: Zakat Fund; Profitability; Mudharabah Income; Wadiah Bonus